The Effect of Video-Based Education on Knowledge, Attitudes, and Preventive Practices Regarding High-Risk Pregnancy Among Pregnant Women - Eppy Setiyowati; Sumiatin Sumiatin; Winarti Winarti; Rudi Hartono (Indonesian Journal of Global Health Research, 2026)
High-risk pregnancy is a dangerous condition because it can lead to an increase in maternal and fetal mortality. Factors such as knowledge, education, environment, habitual behavior and socio-culture as well as the constrained delivery of health information are the causes of high-risk pregnancy. The general objective of this study was to explain the influence of video education on behavior in preventing high-risk pregnancies. Quasi Pre-Experimental with 33 pregnant women in the control group and 33 pregnant women with purposive sampling which was carried out in the Walikukun Health Center. This study covers the dependent variable, namely behavior (knowledge, attitudes, and actions) of high-risk pregnancy prevention and independent variables of education through videos. Statistical analysis of the study using Wilcoxon Signed Rank Test and Mann-Whitney U Test. The results of the study showed that there was effect of education through video on knowledge (p value= 0.000, attitude (p value = 0.000) and actions (p value 0.003) (p <0.05) on the prevention of high-risk pregnancy in pregnant women . in preventing high-risk pregnancies.